2017
DOI: 10.19044/esj.2017.v13n31p185
|View full text |Cite
|
Sign up to set email alerts
|

International Trading Prices Of India’s Oilseed Crops: Growth Rates, Elasticities And Foreign Trade Policy

Abstract: World prices influence international trade and so economic precision is required. This foreign trade research study examines exports and imports of India's major oilseeds from 1990-91 to 2015-16. The methodology employed is the estimation of CAGR, Instability Index, Export import price elasticities of oilseeds and identification of top export import destinations. The results show that export prices of groundnut, soybean, niger, safflower, sesamum and sunflower were higher than import prices indicating that Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The rice witnessed high export elasticities. Export–import prices of all cereals were unstable (Dastagiri et al, 2018). Dastagiri et al (2021) found that, globally, the export price elasticity was inelastic in all countries of grapes, oranges, and bananas except Italy in oranges and Panama in bananas, 1990–2018.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rice witnessed high export elasticities. Export–import prices of all cereals were unstable (Dastagiri et al, 2018). Dastagiri et al (2021) found that, globally, the export price elasticity was inelastic in all countries of grapes, oranges, and bananas except Italy in oranges and Panama in bananas, 1990–2018.…”
Section: Resultsmentioning
confidence: 99%
“…The study found that export price elasticity of mangoes was marginally higher in the Spain and the Netherlands. Dastagiri et al (2020) found that, globally, import prices of coffee and tea were higher than export prices during 1990-1991 to 2017-2018. Globally, export price elasticities of coffee in MERCOSUR and COMESA were marginally higher than import price elasticity (Dastagiri et al, 2020).…”
Section: 41mentioning
confidence: 99%
See 1 more Smart Citation